Reversible repression of papillomavirus oncogene expression in cervical carcinoma cells: consequences for the phenotype and E6-p53 and E7-pRB interactions. - von Knebel Doeberitz, M (J Virol, 1994)
The transforming genes E6 and E7 of high-risk human papillomaviruses are consistently expressed in papillomavirus-associated neoplasms of the anogenital tract. In papillomavirus type 18-associated SW 756 cervical carcinoma cells, transcription of the viral E6-E7 genes is blocked by dexamethasone. Herein we show that dexamethasone-mediated repression of the E6-E7 genes results in loss of the neoplastic phenotype of SW 756 cells. Withdrawal of dexamethasone restores E6-E7 expression and neoplastic growth. Moreover, reconstitution of E6-E7 gene expression by a dexamethasone-inducible expression vector renders the neoplastic phenotype resistant to dexamethasone. These results clearly indicate that the continuous expression of the viral E6-E7 oncogenes is required to maintain the neoplastic growth properties of SW 756 cervical cancer cells. The viral E6 protein destabilizes the p53 tumor suppressor gene product in vitro. Since low levels of p53 have been observed in papillomavirus-transformed keratinocyte cell lines, it was speculated that degradation of p53 by E6 contributes to papillomavirus-associated growth deregulation. Consistent with this hypothesis, we detected a significant increase in p53 levels upon dexamethasone-induced repression of papillomavirus E6-E7 oncogene expression. No p53 increase was observed in dexamethasone-treated cells in which the viral oncogene expression was restored. The viral E7 protein has been shown to complex with the retinoblastoma tumor suppressor gene product (pRB). In some cells, this interaction has been shown shown to release the transcription factor E2F from its complex with pRB, and it has been hypothesized that E7-induced, increased levels of free E2F contribute to the transforming potential of the viral oncogenes. In gel shift experiments, we detected relatively stable complexes of pRB and E2F in all SW 756-derived cells, independent of the level of E7 expression. This suggests that E7-mediated release of E2F from its complex with pRB might not be required to maintain the neoplastic phenotype of human papillomavirus-associated cancer cells, although a possibly relevant partial E7-mediated release of E2F from pRB cannot be excluded. IMAGES: